BER Performance of 4x1 Space-Time Parallel Block Coded Two-Path OFDM Systems - Yeh, Hen-Geul; Zhou, Jun (Proceedings / Wireless Telecommunications Symposium, 2022)
In this paper, a 4x1 space-time (ST) orthogonal frequency division multiplexing (OFDM) system is proposed with parallel cancellation (PC) to form a 4x1 STPC-OFDM system. The 4x1 STPC-OFDM system mitigates the inter-carrier interference (ICI) in the mobile channels due to the two-path block coding approach in PC scheme. Furthermore, a generalized STPC architecture can also be designed with multiple receiver antennas. It offers higher diversity and better BER performance. The orthogonal transforms, Zadoff-Chu transform (ZCT) and Walsh-Hadamard transform (WHT) can be employed as a precoder to enhance the BER further. Although the proposed STPC-OFDM systems require two-path transmission, simulations demonstrate that the proposed 4x1 STPC-OFDM full rate systems are more robust to the frequency selective channels and have a better BER performance than that of a half rate ST-OFDM system with the same bandwidth efficiency. Moreover, it regains the bandwidth efficiency and still has a better BER for fair data rate comparison with 4x1 ST-OFDM when using a high modulation index.